THE APPLICATION OF SCIENTIFIC APPROACH TO IMPROVE CRITICAL THINKING ABILITY THROUGH JUNIOR HIGH SCHOOL STUDENTS - Agung Maulana; Hendra Gunawan; Nurlis Solihah; Dindin Syarif Nurwahyudin (Journal Of Educational Experts (JEE), 2018)
This research aims to check the critical and mathematical thinking ability through junior high school students with using scientific approach. In addition, it aims to check the improvement of critical and mathematical thinking though junior high school students. The method used on this research was quasy experiment which was designed to nonequivalent control group. The population on this research was all the junior high school students of Penida Katapang Junior high School Bandung Regency. The Sample was two classes of 7th grade. The data was attained by critical thinking and mathematical test which using material of shapes.